(untitled) (Revista de História Regional, 2007)
The Diocesis of Ponta Grossa was created in 1930, when its first bishop, D. Antonio Mazzarotto was appointed. A well-known preacher, with innate eloquence, he built an image of authority and fought for the truths of faith which he expressed in sermons, pastoral visits and also through pastoral letters. In them he registered a program for the Diocese, a sacred placed crossed by multiple conflicts and different views of the world, in an effort towards normatizing and unifying it.